TIKTOK’S SPIRAL OF ANTISEMITISM: A STUDY CASE IN INDONESIA - Nathanael, Garcia Krisnando; Sadjijo, Priyono; Saputra, Windhi Tia; Sutowo, Irpan Ripa’i (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2023)
With its disruptive development as the biggest social media worldwide, TikTok poses numerous threats to the society. With 99 million users in Indonesia, TikTok has potential to propagate hate speech on its platform. Having rich history of antisemitism in Indonesia, researcher seek to identify whether TikTok propagate antisemitism in Indonesia. In order to conduct the research, quantitative methods are utilized. This research focused on antisemitism on TikTok in Indonesia, which can be perceived as cyberbullying and online hate speech, and aimed to explain how TikTok used in Indonesia, forms of antisemitism on TikTok in Indonesia (if any), and how antisemitism proliferate through TikTok. Hence, the research would attempt to verify whether TikTok propagate antisemitism in Indonesia. In order to analyze and get a better view of the theme, researcher will discuss the rise of TikTok and the phenomena of Antisemitism in Indonesia in the next sections. With 400 samples, it is found that TikTok is having a great screen time (more than 60 minutes per day) and enjoyed by most of their users in Indonesia and it is indicated that TikTok able to convey political messages/social campaign efficiently in Indonesia. This research concludes that TikTok does propagate antisemitism in Indonesia, despite its sprawling are limited.